Changes in virus-transmission habits during the COVID-19 pandemic: a cross-national, repeated measures study - Rebar, AL; Lally, P; Verplanken, B; Diefenbacher, S; Kwasnicka, D; Rhodes, RE; Lanzini, P; Koutoukidis, D; Venema, TAG; Gardner, B (Taylor and Francis, 2022)
Objective: The COVID-19 pandemic saw promotion of novel virus transmission-reduction behaviours, and discouragement of familiar transmission-conducive behaviours. Understanding changes in the automatic nature of such behaviours is important, because habitual behaviours may be more easily reactivated in future outbreaks and disrupting old habits may discontinue unwanted behaviours.